2020
DOI: 10.3390/su12229597
|View full text |Cite
|
Sign up to set email alerts
|

Contributing Factors in Adolescents’ Mental Well-Being—The Role of Socioeconomic Status, Social Support, and Health Behavior

Abstract: Mental disorders are common in adolescents, and for effective interventions we should be aware of their determinants. However, there are only a small number of studies investigating the combined effect of multiple factors. Therefore, our aim is to assess the impact of socioeconomic status, social support, and health behavior on adolescents’ mental well-being. A cross-sectional health survey of 1641 children was carried out in accordance with the study protocol of the Hungarian Health Behavior in School-aged Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Regarding SS, studies have shown that lower SS is associated with unfavorable mental health among children and adolescents (e.g. ; Aber et al, 2000 ; Nagy-Pénzes et al, 2020 ). It has been proposed that SS predicts access to resources, which in turn may influence mental health (Mackenbach, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding SS, studies have shown that lower SS is associated with unfavorable mental health among children and adolescents (e.g. ; Aber et al, 2000 ; Nagy-Pénzes et al, 2020 ). It has been proposed that SS predicts access to resources, which in turn may influence mental health (Mackenbach, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Social support, socioeconomic status (SES), and health behaviors are affecting factors that concern nutritional status and could influence mental health [ 10 , 11 ]. Therefore, along with various factors, diet is a critical modifiable factor that appears to have a vital role in psychological status [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents, who are at high risk for mental health problems, began to experience stress, emotional conflicts, fear, and a sudden change in routine more intensely than people in other age groups [ 3 , 4 ]. Among mental health problems, depression was already the most common mental disorder in adolescents, even before the global health crisis [ 5 ]. As if the age of vulnerability that is adolescence was not enough by itself, with the pandemic, many of these young people began to experience an increase in anxiety and depressive symptoms, associated with overlapping risk factors [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%